Relación de largo plazo y análisis de causalidad y sensibilidad entre los salarios reales y la productividad laboral en el sector manufacturero a partir de cifras de los departamentos en Colombia (2014)
This article focuses on identifying the relation between wages and productivity. To demonstrate if there is a long-term relation between these variables, unit root and cointegration tests were applied to determine if the series shared common stochastic tendencies. A vector autoregressive model (VAR) was used to do a causality and sensitivity analysis to determine the future effect of the shocks in any variable of the system, on itself and others. To conduct the empirical exercise, series of productivity and wages from 24 Colombian regions were used, which were calculated from the annual manufacturing survey. The empirical findings allow to conclude that a distribution of wealth conflict exists in Colombia because changes in productivity are not reflected on workers' real salaries growths. On the other hand, increasing the actual wage is not advisable for business owners, as that growth does not have a future positive effect on productivity